English idioms : exercises on idioms - Seidl, Jennifer. (Oxford University Press, 1989)
Key words with idiomatic uses. Idioms with nouns and adjectives. Idiomatic pairs. Idioms with prepositions. Phrasal verbs. Verbal idioms. Idioms from special subjects...